Expression of asprosin in rat hepatic, renal, heart, gastric, testicular and brain tissues and its changes in a streptozotocin-induced diabetes mellitus model - Kocaman, Nevin; Kuloglu, Tuncay (Churchill Livingstone, 2020)
In this study, we aimed to investigate the presence of asprosin (ASP) in the liver, kidneys, heart, stomach, testicles and brain and to determine the serum and tissue asprosin levels in diabetic rats. A total of 14 male Wistar Albino rats were divided into two groups, each containing 7 rats: (I) control group and (II) experimental diabetes group. Control rats received no treatment and the rats in the experiment group received single-dose of streptozotocin (STZ) (50 mg/kg) dissolved in 0.1 M sodium citrate buffer (pH: 4.5) intraperitoneally. Serum levels of asprosin were measured using ELISA method. The presence of asprosin in hepatic, renal, cardiac, gastric, testicular and brain tissues was investigated using immunohistochemical staining. Asprosin was detected in hepatocytes in the liver, cortical distal tubule cells in the kidney, cardiomyocytes in heart, surface epithelial cells of stomach fundus, interstitial Leydig cells in testes and cortical neurons of the brain. Compared to control group, it was found that diabetic rats had decreased asprosin levels in liver, kidney and heart tissues, increased levels in gastric and testicular tissues and no significant changes in brain tissue. Serum asprosin levels of diabetic rats were found to be decreased compared to the control group. This is the first study in the literature that reports the presence of asprosin in liver, kidney, heart, stomach, testis and brain tissues in rats. The aim of the study is to determine the presence of ASP, a newly discovered adipokine, in various tissues and to examine tissue and serum level changes in STZ-induced diabetes.
Keywords: Asprosin; Diabetes mellitus; Immunohistochemistry; Streptozotocin